Pengaruh Model Pembelajaran Quantum Writing terhadap Kemampuan Menulis Kreatif Puisi pada Siswa Kelas X SMA Negeri 1 Pedamaran Timur - Kusniati Kusniati; Misriani Misriani; Dessy Wardiah (Journal on Education, 2023)
This study aims to determine whether there is an effect of the quantum writing model on the ability to write poetry creatively in class X.1 students of SMA Negeri I Pedamaran Timur. The population in this study were all students of class X.I SMA Negeri I Pedamaran Timur, consisting of 36 students. The sample in this study was obtained using cluster random sampling technique. So that class X.1 was selected with a total of 36 students as the experimental class and X.2 with a total of 31 students as the control class. This research model uses an experimental model. The data analysis technique used is the test data analysis technique, observation interview test. The results of this study indicate that the average value of the pretest control class was not treated with quantum writing or by learning ordinary material which obtained scores of 21 and 24 while for the posttest experimental class group with quantum writing treatment 59 and a greater value of 61. This proves that there is an influence of the Quantum Writing Model on the Ability to Write Creative Poetry for Class X SMA Negeri I Pedamaran Timur. So the hypothesis in the research proved true. Based on the criteria for testing the hypothesis that HO is rejected if t count ≤ t table, and Ha is accepted if t count ≥ t table, with = 4.287 and 1.671. This proves that t count ≥ t table with a value of 4.287 ≥ 1.671 then Ha in this study is accepted as true.